2021
DOI: 10.1002/biot.202000250
|View full text |Cite
|
Sign up to set email alerts
|

Biofabrication of a three dimensional human‐based personalized neurofibroma model

Abstract: Neurofibromas are the most characteristic feature of neurofibromatosis type 1 (NF1), a multisystemic disorder caused by aberrations in the neurofibromin gene (NF1). Despite significant progress over the last several years in understanding this disease, a suitable in vitro model to better mimic neurofibroma formation and growth has yet to be described. There is therefore a need to establish an in vitro, three dimensional model that allows the incorporation of multicellular lineages and the modulation of the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…A more uniform cellular distribution may then help tissue maturation and consequently improve ECM secretion and assembly [32][33][34] . It has been shown that cell-cell and cell-ECM interactions in tissue engineering are needed in disease modeling to better represent crosstalk between cells, tissue compositions and the microenvironment associated to complex human pathologies 11,35,36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more uniform cellular distribution may then help tissue maturation and consequently improve ECM secretion and assembly [32][33][34] . It has been shown that cell-cell and cell-ECM interactions in tissue engineering are needed in disease modeling to better represent crosstalk between cells, tissue compositions and the microenvironment associated to complex human pathologies 11,35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Macroscopic photographs of the biopsied TEBVs junction sites were also taken prior to the histological analysis. Fixed 10 μm TEBV cross-sections were then stained with hematoxylin and eosin (H&E) as previously described 36 . Microscopic images were acquired and measured under bright-field conditions using an upright microscope (AxioImager.M2; Carl Zeiss Microscopy, Jena, TH, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…We showed for the first time that it was possible to differentiate ARSACS-iPSCs into MNs and Purkinje cells using the 3D culture system we developed, as well as to detect some characteristic ARSACS pathological features such as abnormal accumulation of NFM along the neurites. Using collagen sponges populated with dermal fibroblasts as a 3D substrate, which is known to promote long-term survival and neurite elongation of MNs [ 39 ] and to reproduce pathological features observed in other brain diseases such as neurofibromatosis [ 46 ] and amyotrophic lateral sclerosis [ 47 , 48 ], it was possible to enable long term (>53 days) of Purkinje cells and to promote abundant elaborated dendritic ramifications. To better mimic ARSACS cellular microenvironment around MNs, iPSC-derived Schwann cells were also cocultured with iPSC-MNs within the 3D substrate.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, tissue engineering, especially the self-assembly method, can be helpful. For example, models have been developed to study skin pathologies such as hypertrophic scars [53], systemic sclerosis (scleroderma) [54], melanoma [55,56], psoriasis [57], epidermolysis bullosa [58], neurofibromatosis [59], or skin manifestations of amyotrophic lateral sclerosis (ALS) [60], but also genitourinary pathologies such as vaginal mucosa infection by the human immunodeficiency virus (HIV) [61], ketamine-induced cystitis [62], bladder cancer [63] or urinary tract infection [64].…”
Section: The Self-assembly Techniquementioning
confidence: 99%